On the practices of risk re-normalisation - Vidmar, Matjaž (Teorija in praksa, 2019)
This paper outlines a series of observations about how public discourse is framed regarding the way risk assessment is conceived at the cutting edge of developing the scientific and technological frontier. Examining the newly emerging narratives concerning the future of outer space exploration and industry, particularly human missions to and settlements on Mars, I propose the concept of "risk re-normalisation" as a major tool for reframing various aspects of the public discourse on risk through the premediation of visions and imaginaries. Specifically, as the risk-assessment discourse evolves, seemingly separate actors' under- and over-statements of hazards are used in public discourse to create a set of limiting parameters, thereby creating a more favourable risk governance environment for the further advancement of Space Exploration. This is underpinned by the discursive symbiosis of private and public spheres, once their rhetorical separation is achieved through boundary work.
Keywords: analiza diskurza; javni diskurz; raziskovanje vesolja; tehnologija; tveganje